2008
DOI: 10.1002/glia.20808
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic calcium signals induced by neuromodulators via functional metabotropic receptors in the ventral respiratory group of neonatal mice

Abstract: A controlled, periodic exchange of air between lungs and atmosphere requires a neuronal rhythm generated by a network of neurons in the ventral respiratory group (VRG) of the brainstem. Glial cells, e.g. astrocytes, have been shown to be supportive in stabilizing this neuronal activity in the central nervous system during development. In addition, a variety of neuromodulators including serotonin (5-HT), Substance P (SP), and thyrotropin-releasing hormone (TRH) stimulate respiratory neurons directly. If astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 93 publications
1
23
1
Order By: Relevance
“…In addition, glia cultured from the preBötC have minimal SP sensitivity (Fig. 6), which is consistent with recent observations in slices that only a portion of glia in the preBötC region respond to SP with small increases in intracellular Ca 2ϩ (Härtel et al, 2009). Furthermore, while cultured glia express NK1R mRNA (Too et al, 1994), glia in guinea pig (Yip and Chahl, 2001) and human brain (Tooney et al, 2000) do not express NK1R protein.…”
Section: )supporting
confidence: 91%
“…In addition, glia cultured from the preBötC have minimal SP sensitivity (Fig. 6), which is consistent with recent observations in slices that only a portion of glia in the preBötC region respond to SP with small increases in intracellular Ca 2ϩ (Härtel et al, 2009). Furthermore, while cultured glia express NK1R mRNA (Too et al, 1994), glia in guinea pig (Yip and Chahl, 2001) and human brain (Tooney et al, 2000) do not express NK1R protein.…”
Section: )supporting
confidence: 91%
“…Astrocytes in the preBötC network are responsive to glutamate [22] and Ca 2+ transients can be evoked by application of glutamate [15], [23]. In this paper we were able to show that metabotropic glutamate receptors coupled to the PLC/IP3 pathway play a role for glutamate induced astroglial calcium signaling in the preBötC.…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies from this laboratory demonstrated that glutamate triggers calcium signaling in astrocytes of the ventral respiratory region of the medulla [15], [23], and other studies have shown that group I metabotropic glutamate receptors promote calcium release from intracellular stores and couple neuronal activity to calcium signals in nearby astrocytes of rat cortex, hippocampus and suprachiasmatic nucleus [24], [25].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations